Associations between lipodystrophy or antiretroviral medications and cirrhosis in patients with HIV infection or HIV/HCV coinfection. Issue 5 (May 2015) - Ioannou, George N.; Bryson, Christopher L.; Weiss, Noel S.; Boyko, Edward J.
Abstract : Background: Many HIV antiretroviral medications have been associated with chronic liver injury. HIV-infected patients frequently develop HIV and highly active antiretroviral treatment-associated lipodystrophy syndrome (HALS), characterized by accumulation of intra-abdominal fat, insulin resistance, and hepatic steatosis. We sought to determine whether long-term exposure to specific antiretroviral medications or the presence of HALS predispose HIV-infected patients to the development of cirrhosis. Methods: HIV-infected patients with cirrhosis who received care in the Veterans Affairs Healthcare System nationally in 2009 were matched by hepatitis C virus (HCV) coinfection status and year of first visit for HIV to the Veterans Affairs Healthcare System with HIV-infected patients without cirrhosis in a 1 : 3 ratio. Results: Among HIV/HCV coinfected patients (593 with cirrhosis and 1591 matched controls), HALS was associated with a significantly increased risk for cirrhosis (adjusted odds ratio 1.6, 95% confidence interval 1.1–2.3), especially among Black patients (adjusted odds ratio 2.9, 95% confidence interval 1.6–5.2). In addition, among HIV/HCV coinfected patients, longer cumulative exposures to all antiretroviral medications, all nucleoside reverse transcriptase inhibitors, all protease inhibitors, and selected individual medications (didanosine, stavudine, and nelfinavir) were found to be significantly associated with cirrhosis. In contrast, among HIV-infected patients not coinfected with HCV (245 with cirrhosis and 658 matched controls), HALS or exposure to antiretroviral medications was found not to be significantly associated with cirrhosis, with the exception of didanosine. Conclusion: HALS and cumulative exposure to nucleoside reverse transcriptase inhibitors and protease inhibitors, especially stavudine, didanosine, and nelfinavir, were found to be associated with the development of cirrhosis in HIV/HCV coinfected patients, but not in HIV-monoinfected patients.